Usability and Acceptability of Home-based Self-testing for Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Antibodies for Population Surveillance. (12th August 2020) - Atchison, Christina; Pristerà, Philippa; Cooper, Emily; Papageorgiou, Vasiliki; Redd, Rozlyn; Piggin, Maria; Flower, Barnaby; Fontana, Gianluca; Satkunarajah, Sutha; Ashrafian, Hutan; Lawrence-Jones, Anna; Naar, Lenny; et al.
Abstract: Background: This study assesses acceptability and usability of home-based self-testing for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibodies using lateral flow immunoassays (LFIA). Methods: We carried out public involvement and pilot testing in 315 volunteers to improve usability. Feedback was obtained through online discussions, questionnaires, observations, and interviews of people who tried the test at home. This informed the design of a nationally representative survey of adults in England using two LFIAs (LFIA1 and LFIA2) which were sent to 10 600 and 3800 participants, respectively, who provided further feedback. Results: Public involvement and pilot testing showed high levels of acceptability, but limitations with the usability of kits. Most people reported completing the test; however, they identified difficulties with practical aspects of the kit, particularly the lancet and pipette, a need for clearer instructions and more guidance on interpretation of results. In the national study, 99.3% (8693/8754) of LFIA1 and 98.4% (2911/2957) of LFIA2 respondents attempted the test and 97.5% and 97.8% of respondents completed it, respectively. Most found the instructions easy to understand, but some reported difficulties using the pipette (LFIA1: 17.7%) and applying the blood drop to the cassette (LFIA2: 31.3%). Most respondents obtained a valid result (LFIA1: 91.5%; LFIA2: 94.4%). Overall there was substantial concordance between participant and clinician interpreted results (kappa: LFIA1 0.72; LFIA2 0.89). Conclusions: Impactful public involvement is feasible in a rapid response setting. Home self-testing with LFIAs can be used with a high degree of acceptability and usability by adults, making them a good option for use in seroprevalence surveys. Abstract : We found high levels of usability and acceptability among adults living in England, UK, of at-home self-testing with lateral flow immunoassays for severe acute respiratory syndrome coronavirus 2 antibodies. The tests provide an attractive solution for conducting large seroprevalence surveys in the community.